One pot environmental friendly - Heba H. El-Maghrabi; Engy Ahmed Nada; Fathi S. Soliman; Yasser Mohamed Moustafa; Alaa El-Sayed Amin (Egyptian Journal of Petroleum)
A nanocomposite synthesis of TiO2NT-graphene was prepared from titanium dioxide nanotubes and graphene oxide (GO) by a simple environmental friendly method (green method). The structure, surface morphology and chemical composition were characterized by Fourier-transform infrared spectroscopy (FT-IR), X-ray diffract meter (XRD), Raman, energy dispersive X-ray spectrometer (EDS), transmission electron microscopy (TEM), and selected area electron diffraction(SAED). XRD results confirm the interaction of TiO2-NT with graphene. A fast decomposition of the phenol was observed with a degradation efficiency of 70.6% within 180 min.